Studi Meta-analisis Hipertensi dan Diabetes Melitus Sebagai Faktor Risiko Penyakit Ginjal Kronis di Indonesia - Rani, Maha; Pramana, Ida Bagus Putra; Oka, Anak Agung Gde (Universitas Udayana, 2022)
Indonesia is currently experiencing double burden of disease which Chronic Kidney Disease (CKD) is one of Indonesian disease burdens. Hypertension and Diabetes Mellitus are risk factors for CKD that have been widely studied, it is necessary to carry out a meta-analysis study in order to obtain stronger data and also could be used as a reference to prevent CKD. This study uses Systematic Review and Meta-analysis with RevMan 5.4.1. Estimated data using the Random Effect Model from 5 Case Control Studies with 781 case samples and 781 control samples. The OR for Hypertension for CKD was 5.28 (95% CI 1.46 - 19.09) while the OR for Diabetes Mellitus was 3.34 (95% CI 1.79 - 6.25). It can be interpreted that individuals with Hypertension have 5.28 times higher risk of experiencing CKD than non-Hypertensive individuals whereas individuals with Diabetes Mellitus have 3.34 times higher risk of developing CKD than individuals without Diabetes Mellitus.